Expression of p53, p63, podoplanin and Ki-67 in recurring versus non-recurring oral leukoplakia - Jonas Sundberg; Sushma Pandey; Daniel Giglio; Erik Holmberg; Göran Kjeller; Anikó Kovács; Lars Peter Sand; Burcu Tokozlu; Jenny Öhman; Dipak Sapkota; Bengt Hasséus (Scientific Reports, 2021)
Abstract Oral leukoplakia (OL), a potentially malignant disorder, recurs in 40% of cases after surgical removal. Recurrence is a risk factor for malignant transformation. We aimed to examine the prognostic significance of four biomarkers related to cell proliferation: p53, p63, podoplanin (PDPN) and Ki-67 in predicting recurrence. Formalin-fixed-paraffin-embedded specimens from excised OL (n = 73, 33 recurrent; 40 non-recurrent) were collected in a prospective study. Immunohistochemistry was used to visualise expression of p53, p63, PDPN and Ki-67. Image analysis software was used for quantification of p53-, p63- and Ki-67-expressing cells, while PDPN was analysed visually. The expression of all four proteins were higher in recurrent compared with non-recurrent OL, only expression of p53 was statistically significant. In uni- and multivariable Cox regression analyses of individual markers, expression of p63 was significantly associated with higher recurrence risk (p = 0.047). OL with a combined high expression of both p53 and p63 had a significantly higher risk to recur [Log Rank, p = 0.036; multivariate Cox, HR: 2.48 (1.13–5.44; p = 0.024)]. Combination of p53 and p63 expression may be used as a prognostic biomarker for recurrence of OL.